Peran Nabi Muhmmad SAW sebagai Kepala Agama di Makkah dan Kepala Negara di Madinah - Muhammad Faisal; Ansar Tohe (Al-Kindi, 2026)
This study aims to analyze the transformation of Prophet Muhammad's (peace be upon him) leadership from his role as a religious leader in Mecca to his dual role as both religious and political leader in Medina, as well as to examine its relevance to contemporary concepts of leadership and governance. The research employed a qualitative approach using library research by analyzing primary and secondary sources, including the Qur'an, Hadith, classical sīrah literature, books, and scholarly journal articles. Data were collected through documentation techniques and analyzed descriptively using data reduction, data presentation, and conclusion drawing. The findings reveal that the Prophet's leadership developed in response to changing social and political circumstances without altering the fundamental objectives of Islam. During the Meccan period, his leadership emphasized faith, moral education, and spiritual development, while in Medina it evolved into an integrated model combining religious guidance with state administration through principles of justice, consultation (shūrā), equality, and social welfare, as reflected in the Constitution of Medina. The study concludes that the Prophet's leadership represents a contextual and adaptive model whose universal values remain relevant for contemporary governance while allowing institutional flexibility according to societal needs.